Wasp-waisted magnetism in hydrothermally grown MoS2 nanoflakes. (11th November 2016) - Chacko, Levna; Swetha, A K; Anjana, R; Jayaraj, M K; Aneesh, P M
Abstract: Two-dimensional semiconducting materials are emanating as a requisite group of materials for future nanoscale electronics and optoelectronics. Particularly, transition-metal dichalcogenides like molybdenum disulphide (MoS2 ), a semiconducting inorganic counterpart of graphene have intrigued intensive interest as two-dimensional materials due to its novel functionalities. In this work, the utilization of high pressure and low temperature hydrothermal method offers a facile, versatile synthetic tool for MoS2 nanoflakes formation without the addition of any surfactants. Our experimental results resolve the formation of hexagonal phase, well-ordered stacking of S–Mo–S layers, quantum confinement and interlayer interaction. The strong spin–orbit coupling in MoS2 provides enthralling optical and magnetic properties. A large optical absorption in 400–700 nm region and strong luminescence provide evidence for the indirect to direct band gap transition in MoS2 . Magnetic measurement results reveal ferromagnetism for all the MoS2 nanoflakes and also indicate an increase in saturation magnetization with increase in duration of growth. In addition, a wasp-waisted hysteresis loop was also observed for the first time in MoS2 nanostructures indicating multimodal population, increased grain growth and MoS2 –MoO3 coupling. Our findings provide important insights into the future applications of MoS2 in high-performance nanodevices and spintronics.